168k views
2 votes
Rewrite the function f(x)=-2(x+2)^2+6 in the form f(x)=ax^2+bx+c

User Selby
by
4.5k points

1 Answer

1 vote

Answer:

f(x) = -2x² - 8x - 2

General Formulas and Concepts:

  • Order of Operations: BPEMDAS
  • Expand by FOIL (First Outside Inside Last)
  • Standard Form: f(x) = ax² + bx + c
  • Vertex Form: f(x) = a(bx + c)² + d

Explanation:

Step 1: Define function

Vertex Form: f(x) = -2(x + 2)² + 6

Step 2: Find Standard Form

  1. Expand by FOILing: f(x) = -2(x² + 4x + 4) + 6
  2. Distribute -2: f(x) = -2x² - 8x - 8 + 6
  3. Combine like terms (constants): f(x) = -2x² - 8x - 2
User Keimeno
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.